Sistem Pendukung Keputusan Rekomendasi Supplier Bahan Baku Kerupuk Rambak Tapioka Terbaik Menggunakan Metode Evaluation Based On Distance From Average Solution (EDAS) - Prayitno, Heru; Rozi, Anief Fauzan (Jurnal Sains dan Teknologi (JSIT), 2022)
Kerupuk (Crackers ) are one of the specialties of the Indonesian people and are well-known by all social classes, from the lower to the upper middle classes. Most Indonesians consume crackers because they are delicious and can be consumed with any meal. This resulted in the proliferation of cracker manufacturers in Indonesia, not only producing a single type of cracker but also a variety of crackers whose flavor and ingredients were adapted to the palate of the Indonesian people. Crackers made from leather or Rambak crackers are well-known among the general population. Rambak crackers are not significantly distinct from other types of crackers. The difference is in the ingredients. Rambak crackers are made from various ingredients, including cow, buffalo, rabbit, chicken, fish, tapioca flour, and flour. In making these Rambak crackers, however, cowhide is typically employed. Cow leather is one of the products of the livestock sector, which, according to the Central Statistics Agency of Jember Regency, produced 11,287 pieces of leather in 2019. This demonstrates that Rambak tapioca cracker ingredients are not readily available on the market. Consequently, a Decision Support System (DSS) is a system that can provide problem-solving and communication capabilities in semi-structured and unstructured environments. Positive Distance from Average (PDA) and Negative Distance from Average (NDA) are the two distance measures used in the Evaluation Based on the Distance from Average Solution (EDAS) method. The best alternative will be the one with the highest PDA value and the lowest NDA. Based on the User Acceptance Test (UAT) results of the system, which the Wanteyan Home Industry well received, this decision support system yields 5%.